Evaluating 3D wireless grids as parallel platforms. (2015) - Kamali, Amir Mansoor; Bailey, Christopher; Austin, Jim
Wireless connections have not been good choices for connecting processors in a massively parallel computer; mainly because of their higher energy demands and lower data rates compared to wireline. In light of recent developments in wireless technologies, this paper investigates if (and, to what extent) that assumption is still valid. Capacitive coupling, inductive coupling and on-chip radio technologies are reviewed to know how close we are to an efficient wireless parallel computer, especially in terms of energy consumption and data rate. For an evaluation case we utilise a simulated 3D wireless grid as a parallel platform, the 'Ball Computer'. We test the viability of a concept 3D wireless interconnect network for a supercomputer. The behaviour of the proposed platform under different situations are studied using simulation results. We have identified challenges for the second stage of the long-term goal to build a prototype of Ball Computer.